Complete mitochondrial genome of Quercus variabilis (Fagales, Fagaceae) - Quanxin Bi; Dongxing Li; Yang Zhao; Mengke Wang; Yingchao Li; Xiaojuan Liu; Libing Wang; Haiyan Yu (Mitochondrial DNA. Part B. Resources, 2019)
Quercus variabilis (Chinese cork oak) is an economically valuable oak as the source of industrial cork, which was widely distributed in eastern Asia. In this study, the complete mitochondrial genome of Q. variabilis was sequenced using the Illumina Hiseq and PacBio Sequel technique. The mitogenome is 412,886 bp in length and the GC content is 45.76%. The genome consists of 36 protein-coding genes, 3 ribosomal-RNA genes, and 21 transfer-RNA genes. Phylogenetic analysis based on protein-coding genes showed that Q. variabilis was close to the species in the Cucurbitaceae family.